Silk Road as a symbol of yin and yang harmony, female and male searching (based on the novel “The Bridge Through Eternity” by R.Bach (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Pronkina Olga (奥莉娅, 兰州城市学院), Lanzhou City University discovers symbolism of the Great Silk Road. It is a symbol of unification of Yin and Yang, Male and Female, West and East. R. Bach's Novel «Bridge though the infinity» shows, that being on the Silk Road person try to find himself, his love and his second half. Richard thought, that soul mates are united in a harmony of Yin and yang, West and East, Male and Female, Infinite and Changeable, they are both find a sense of life, only being together with each other.
Keywords: thought; literature study; worldview; poetics; psychological; cognitive; novels